Diabetic cystopathy due to detrusor muscle dysfunction in a child with type Ⅰ diabetes mellitus - Parmar, Ankita; Kavthekar, Saiprasad O.; Kulkarni, Suhas P.; M., Sundharavel; Kulkarni, Shradha K.; Pawar, Ravindra S.; Patil, Nivedita B. (International Journal of Contemporary Pediatrics, 2024)
The word diabetic cystopathy (DC) refers to lower urinary symptoms due to diabetic neuromyopathy and is common in adults while very unusual in children with diabetes mellitus. This case report seeks to delineate a distinctive case concerning a 9-year-old boy who was diagnosed with DC due to detrusor muscle dysfunction confirmed by urodynamic studies, induced by type 1 diabetes mellitus of four years duration. DC should be considered in children with long standing urinary symptoms without urinary tract infection in type 1 diabetes mellitus even if it is rare condition.